Organizing organic: Conflict and compromise in an emerging market - haedicke, Michael A. (Stanford Stanford University Press, 2016)
Stakeholders in the organic food movement agree that it has the potential to transform our food system, and yet there is little consensus about what this transformation should look like. Tracing the history of the organic food sector, Michael Haedicke charts the development of two narratives that do more than simply polarise the organic debate, they give way to competing institutional logics.